Laboratory determination of smear and transition zones due to prefabricated vertical drain installation - Sengul, Tayfun; Edil, Tuncer; Ozaydin, Kutay (TAYLOR & FRANCIS INC, 2017)
The smear zone, which develops during the placement of the prefabricated vertical drain (PVD) in the ground using a steel mandrel, is a significant factor that influences the performance of PVDs. The determination of the width and hydraulic conductivity of smear zone is an important consideration in designing ground improvement by preloading with PVDs. Thus, the extent and hydraulic conductivity of the PVD smear zone have received significant attention; however, there is still uncertainty and the topic remains discrepant among investigators. There is limited or no smear zone hydraulic conductivity data that is directly produced by laboratory or field tests. In this study, a laboratory smear zone model experiment that was developed as a performance test for determining the extent of the smear zone and measuring directly its hydraulic conductivity was used. Based on the findings obtained from two different materials (Craney Island dredgings and Hydrite R kaolinite soil), it is indicated that the disturbed zone is made up of two areas, namely smear zone and transition zone, and that the hydraulic conductivity in these areas is lower than the undisturbed soil. The ratio of the hydraulic conductivity of the smear and transition zones to that of the undisturbed soil was found to vary between 0.32 and 0.50 and between 0.57 and 0.82, respectively in different soils. The diameter of the smear zone was found to be 2.3-3.3 times higher than the equivalent diameter of the mandrel depending on the soil. The diameter of the transition zone extended 5.2-7.3 times the equivalent diameter of mandrel again depending on the soil. These directly measured values, in general, are supportive of the published values based on indirect means and the test device can be used to study the impact of mandrels of different size and shape and other factors by minor modification.
Keywords: Craney Island dredgings; disturbed zone; prefabricated vertical drains; smear zone; smear zone effect model testing; transition zone; SOFT BANGKOK CLAY; LAYERED SOIL; PERFORMANCE; IMPROVEMENT; SEEPAGE; MODEL; Engineering; Oceanography; Mining & Mineral Processing